Sensor capacitivo multieletrodo para monitoramento de nível em separadores multifásicos - Säuberlich, Avner Ostrovski (2019)
With the increasing production demand of the oil industry, it is more and more necessary to develop and improve systems, technologies and processes within their various stages. Among them, one important process is the separation of the oil, water and natural gas from the reservoirs at processing plants. At this stage, it is essential to monitor the levels of the different compounds within the separator tanks, so that this information serves as input variable in the control systems ensuring the efficiency and safety of these equipment. Based on this, this work aims to present the study, analysis and testing of a capacitive multielectrode sensor to monitor in real time the level of different fluids in gravitational separators applied in the oil industry. In this way, it is possible to identify the different substances and interfaces present inside separator tanks. In addition, preliminary studies have also been conducted on the combined use of capacitive and inductive monitoring techniques (so that one methodology can address the limitations of the other). The developed prototype was tested in test vessels with satisfactory results for measuring the level of water-oil-air multiphase mixtures. The prototype can be easily installed on test tabs and requires improvements regarding robustness and operation in explosive environments so that it may be used in real applications.